Hubungan Intensitas Aktivitas Fisik dalam Pembelajaran PJOK dengan Tingkat Kebugaran Jasmani Siswa Kelas XI - Heldantara Rifdian Raja; Sapto Wibowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the relationship between physical activity intensity in Physical Education, Sports, and Health (PJOK) learning and the physical fitness level of eleventh-grade students at SMA Negeri 1 Gedangan. This research employed a quantitative method with a descriptive correlational design. The sample consisted of 70 students selected using purposive sampling. Physical activity intensity was measured using a questionnaire, while physical fitness was assessed using the Indonesian Student Fitness Test (Tes Kebugaran Siswa Indonesia/TKSI) Phase F, which includes the T-Test, Beep Test, Vertical Jump, Hand and Eye Coordination Test, Hand Touch Reaction Test, and Dipping Test. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and Pearson Product Moment correlation analysis. The results showed that physical activity intensity was significantly correlated with all components of physical fitness, namely the T-Test (r = -0.446; p < 0.001), Beep Test (r = 0.407; p < 0.001), Vertical Jump (r = 0.568; p < 0.001), Hand and Eye Coordination Test (r = 0.538; p < 0.001), Hand Touch Reaction Test (r = -0.616; p < 0.001), and Dipping Test (r = 0.533; p < 0.001). These findings indicate that higher physical activity intensity is associated with better physical fitness, reflected in improved cardiorespiratory endurance, lower-limb explosive power, coordination, muscular endurance, agility, and reaction speed. Keywords: Physical Activity Intensity, Physical Fitness, Physical Education, High School Students, TKSI